Psychological Impact of Conflict on Women and Girls in Middle Eastern War Zones: A Gender-Specific Analysis - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing (Jurnal Anestesi, 2025)
This study evaluates the psychological impact of conflict on women and girls in Middle Eastern war zones through a systematic meta-analysis of 87 published studies conducted between 2010 and 2024, encompassing 24,583 participants.